2006
DOI: 10.1016/s1726-4901(09)70311-9
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Biopsy in Sarcoidosis

Abstract: Blind and bilateral conjunctival biopsy, due to its ease, safety and specificity, could be the first biopsy inpatients with clinical or chest X-ray abnormalities suggesting sarcoidosis. None of our patients with positive biopsy had nodular lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…Conjunctival tissue biopsy is less invasive than lung biopsy, but controversial results were reported on its diagnostic value. In the last few years, one study has reported on high efficacy of undirected conjunctival biopsy and recommended this procedure as a first biopsy attempt in patient suspected with sarcoidosis (Chung et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctival tissue biopsy is less invasive than lung biopsy, but controversial results were reported on its diagnostic value. In the last few years, one study has reported on high efficacy of undirected conjunctival biopsy and recommended this procedure as a first biopsy attempt in patient suspected with sarcoidosis (Chung et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant variability in the literature, however, the reported age at initial diagnosis varies from ,40 yrs [27,28], to ,40 yrs [29,30] to 48 yrs [31]. Approximately one-third of the patients in the ACCESS study were o50 yrs of age at the time of diagnosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of granulomas with conjunctival biopsy using careful sectioning technique approaches the yield obtained from other tissue sites [16,17], especially when conjunctival pathology such as nodules, follicles, or fibrous scarring is present [4,12,18]. No false positives have been reported in previous studies [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Definitive diagnosis requires histologic evidence of non-caseating, granulomatous inflammation, commonly from biopsy of mediastinal lymph nodes. Another potential biopsy site is the conjunctiva, with a reported diagnostic yield ranging from 20% to 70% with blind biopsies [1-4] and 36% to 75% with directed biopsies [5-8]. This wide range may be explained by different tissue sectioning and analysis techniques; however, few studies describe their histologic methodology.…”
Section: Introductionmentioning
confidence: 99%